Changes in the Abundance and Community Complexity of Soil Nematodes in Two Rice Cultivars Under Elevated Ozone - Wang, Jianqing; Tan, Yunyan; Shao, Yajun; Shi, Xiuzhen; Zhang, Guoyou (Frontiers in Microbiology, 2022)
Global climate changes are characterized by elevated atmospheric ozone concentrations in the surface layer, with important consequences on soil microbial communities and functions. However, the effect of elevated ozone (eO3) on the abundance, diversity, and structural complexity of soil nematode community are elusive under different rice (Oryza sativa L.) varieties. Here, soil nematode community was investigated in two rice varieties (Hybrid, Shanyou 63 vs. Japonica, Wuyujing 3) under open-top chambers (OTC) with control and eO3 conditions. The results showed that the abundance of soil nematode community were altered by eO3, but the responses were dependent on crop varieties. When averaged both varieties, eO3 decreased the total abundance and simplified the network complexity of soil nematode community. By contrast, eO3 increased the abundance of c-p 4 in Shanyou 63, but not in Wuyujing 3, indicating that the hybrid rice variety reversed the adverse impacts of eO3 on the functional group of soil nematodes. Similarly, bacterivores belonging to K-strategy (c-p 4) increased by eO3 in Shanyou 63, suggesting that the soil food web formed a bacteria-dominated channel under eO3 for the hybrid rice variety. This study demonstrated that rice varieties play a critical role in determining the impacts of eO3 on soil micro-food web. Therefore, breeding and biotechnological approaches may become one valuable pathway to improve soil health through shaping the community structures of soil micro-food web in response to climate change in the future.